Critical Thinking Ability as a Correlate of Students’ Mathematics Achievement: A Focus on Ability Level - Darlington Chibueze Duru; Chinedu Victor Obasi (Journal of Instructional Mathematics, 2023)
This study investigated the correlation between critical thinking ability and academic achievement in mathematics among 200 Senior Secondary School Two (SS2) students in Orlu Education Zone in Imo State, Nigeria. The researchers utilized a correlational design and employed a multi-stage but simple random sampling technique to select the sample. Data were collected using two instruments: the Watson-Glaser Critical Thinking Appraisal (WGCTA) and the Mathematics Achievement Proforma (MAP). The validity of the WGCTA instrument was ensured through expert suggestions and guidance. The study addressed three research questions and tested three null hypotheses using the Pearson Product Moment correlation coefficient at a significance level of 0.05. The findings of the study indicated a low positive and significant correlation between critical thinking ability and academic achievement in mathematics for all students. However, there was no significant relationship between critical thinking ability and achievement among high achievers, while there was a significant but negligible positive relationship between critical thinking ability and achievement among low achievers. The study recommended that mathematics teachers should incorporate critical thinking development in their classroom instruction to enhance the critical thinking ability of students, which can lead to improved academic achievement, especially among low achievers.